Kalimat Imperatif dalam Film Yeoljeong-gateun Sori-hago Iss-ne - Ratih Ratna Perdana; Usmi Usmi (JLA (Jurnal Lingua Applicata), 2021)
When communicating, humans as speakers of language will arrange words into meaningful sentences so listeners can understand the purpose of the speech. The speaker will determine the type of sentences and variety of language to use. In the event of spoken communication, there are various types of speech, one of which is imperative sentence speech. This research aims to analyze speech acts that uses imperative sentences in a film entitled Yeoljeong-gateun Soriha-go Iss-ne (열정같은 소리하고 있네). This research applies descriptive method with quantitative and qualitative approaches. Data were collected by applying note-taking techniques. The data were further identified and classified based on the imperative sentence theory by Lee (2016). The result of this study showed that 175 imperative sentences were found in the film corpus. These can be classified into 8 types of speech acts, namely speech acts of commands (43,4%), demands (28,6%), permission (6,9%), suggestion (5,7%), prohibition (5,1%), warning (5,1%), greeting (2,9%), and requests (2,3%). Meanwhile, the most used variety of languages in the film corpus is informal language or haeche with 132 sentences.